Implementasi Peraturan Daerah Nomor 14 Tahun 2012 Tentang Penyelenggaraan Reklame Kota Semarang - Riko Dwi Arnendo; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Semarang’s local government has determined policy about advertisements’s implementation through Spacial Planning department as an implement in advertisement’s implementation policy that head for keeping the beauty of the city that appropiate with spacial planning of Semarang’s city and society’s comfort, but the implementation is still not effective yet. Based on researcher’s invention, known that implementation of the policy isn’t optimum yet and still found some violations. The purpose of this research are for describe and analyze the implementation of advertisement’s implementation policy and for analyze the factors that influence in that implementation. The method used in this research is qualitative-descriptive type. The technique that is used is observation, interview and documentation. Based on research’s result, can be understood that the implementation which has implemented, there is a promoter’s factor, and that factor is communication, but there are some constraint factors which influence the policy. The factors are the resource, bureaucracy’s structure and dispotition which become obstruct of implementation of advertisement’s implementation policy in Semarang City. The reccomendation that writer gives to Spacial Planning Department has a purpose for being better in implementating the advertisement implementation’s policy in Semarang City